Does ESG Disclosure Help Improve Intangible Capital? Evidence From A-Share Listed Companies - Jun, Wu; Shiyong, Zheng; Yi, Tang (Frontiers in Environmental Science, 2022)
With the disclosure of ESG, the investment related to ESG disclosure has increased, and the trend of changes in intangible capital has shown an “inverted S-shaped” curve. The research shows that, in the initial stage of investment in ESG construction, new ESG investments increase intangible capital. With the increase in ESG investment and the advancement of time, the positive effect of the increase in ESG scores on intangible capital begins to appear and gradually offsets the cost of ESG investment. However, when the ESG score of a company is raised to a certain level, the marginal effect of continuing to increase ESG investment will reduce the increase in intangible capital.